Researching national security intelligence: multidisciplinary approaches - Coulthart, Stephen; Landon-Murray, Michael; Van Puyvelde, Damien (Georgetown University Press, 2019)
Introduction : a pluralistic approach to intelligence scholarship / Stephen Coulthart, Michael Landon-Murray, and Damien Van Puyvelde -- Framing intelligence research -- Framing the challenges and opportunities of intelligence studies research / Mark Phythian -- Confessions of an intelligence historian / John Ferris -- Data source and the study of national security intelligence -- The why, who, and how of using qualitative interviews to research intelligence practices / Damien van Puyvelde -- The use of structured behavioral observation systems to address research questions in intelligence / Misty Duke -- A sociological approach to intelligence studies / Bridget Rose Nolan -- Multidisciplinary perspectives on national security intelligence research -- Enhancing political science contributions to american intelligence studies / Stephen Marrin -- Can decision science improve intelligence? -- David R. Mandel -- Charting a research agenda for intelligence studies using public administration and organization theory scholarship / Rick Caceres-Rodriguez and Michael Landon-Murray -- How the field of communication can contribute to the understanding and study of national security intelligence / Rubén Arcos -- Beyond the ivory tower : the research and practice of intelligence -- Bridging the gap the scholar-practitioner divide in intelligence / Brent Durbin -- The ivory tower and the fourth estate / Paul Lashmar -- The ethics of intelligence research / Ross Bellaby -- Conclusion : the past, present, and future of intelligence research / Stephen Coulthart, Michael Landon-Murray, and Damien van Puyvelde -- List of contributors.